EXAMINING THE SIGNIFICANCE OF EFFECTIVELY MANAGING MEETINGS IN AN ORGANISATION - SHONHIWA, DOCTOR CAXTON (IJRDO- Journal of Educational Research, 2017)
This paper examines the significance of effectively managing meetings in the context of aschool. In order to keep track of the work progress, regular meetings can be conducted whereteam members share each other’s development. The whole team is constantly updated with howwell the project goes and what things need to be worked on. Another example is when there arechanges in the school goals. The manager may call for a meeting to discuss the changes with themembers so they are updated with any modifications. On the part of the management,conducting a meeting makes it easy for them to deliver any important updates at one time and atthe same time to the members. Meetings also provide an opportunity for the management toacknowledge the accomplishments of group members through public recognition. Meetings alsohelp group members to reach a common decision when urgent and crucial matters need to bediscussed and brainstormed through personal interaction. Individuals must understand thatmeetings are very essential to the success of the organization. Although a meeting is an integralpart of office routine and some may find it plain and boring in the long run, meetings go beyondachieving goals; they foster and strengthen good working relationships as well.